PENAMBAHAN MINYAK ATSIRI RIMPANG BANGLE (ZINGIBER PURPUREUM ROXB.)SEBAGAI ANTIBAKTERI TERHADAP KARAKTERISTIK SENSORI SABUN CAIR - Wulandari, Dewi; Ali, Akhyar; Ayu, Dewi Fortuna (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The purpose of this study was to determine the quality of sensory and antibacterial activity of liquid soap with the addition of essential oil bangle rhizome. This study used a Complete Randomized Design with five treatments and three replications. The treatments were addition of essential oils in consecutive S0 (0 ml), S1 (0,62 ml), S2 (1,24 ml), S3 (1,86 ml), and S4 (2,5 ml). The data obtained were analyzed statistically using Analysis of Variance dan Duncanâs New Multiple Range Test at 5%. The research showed that addition ofÂ bangle rhizome essential oils significantly effected on antibacterial test, descriptive test and hedonic test. The best treatment of liquid soap in this research was S4 (addition bangle essential oil 2,5 ml) which had antibacterial activity against S. aureus of 3,50 mm dan E. coli of 2,67 mm.The result of descriptive test on liquid soap showed that soap had very bangle scents and hedonic test on liquid soap scents was not favored by the panelists.Â Keywords:Bangle (Zingibeer purpureum Roxb.), essential oil, liquid soap,antibacterial